Edu-2.0: Social Media as Tool of Quality Learning for Underprivileged - Biju., P. R.; Gayathri , 0. (Indian Journal of Educational Technology, 2021)
Choice of social media as a medium for instructions makes it a political weapon for the underprivileged. Impregnated with rigid social hierarchy, where access to quality educational content is inaccessible for the underprivileged people; social media provides enormous 'situations of power' that entail quality content delivery to every doorstep. The co-production of educational contents by millions of users on YouTube, Facebook, biogs, Wikis, and various other platforms require fine-tuning instructional methods and redefining the premises of peer reviewed contents produced by experts and professionals. This review article explores how social media create Edu-2.0 in India; a neologism used in this review article that signifies the proposition that the underprivileged citizens' access to quality educational content has a direct correlation with the co-production of user generated contents on Internet platforms. At present, access to education is worse in India since the logic of a pre-modern social system arbitrates access to education at least for the underprivileged population, say- women, religious minorities and belonging to Scheduled Castes (SCs). This access increases once content delivery significantly endorses social media.